Identifying risk factors associated with worse outcomes in adolescents and young adults undergoing hematopoietic stem cell transplantation. Issue 12 (20th August 2019) - Friend, Brian D.; Tang, Kevin; Markovic, Daniela; Elashoff, David; Moore, Theodore B.; Schiller, Gary J.
Abstract: Background: Adolescents and young adults (AYAs) undergoing allogeneic hematopoietic stem cell transplantation (HSCT) have unique risk factors and poor outcomes when compared to children, but this population has not been well studied. A hematopoietic stem cell transplantation‐comorbidity index (HCT‐CI) has been developed in adults to help predict outcomes, yet this index does not seem suitable for a younger population. Therefore, we sought to examine the prevalence of various risk factors in AYAs undergoing allogeneic HSCT and determine which factors had the greatest impact on overall survival (OS) and treatment‐related mortality (TRM). Procedures: This was accomplished by retrospectively collecting data on 241 patients who received their first allogeneic HSCT at UCLA between 2005 and 2015. We investigated the effect of multiple predictors using the Cox proportional hazards model and Fine and Gray competing risk model for OS and TRM, respectively. Results: Our results showed that AYAs undergoing allogeneic HSCT had poor outcomes, with 5‐year OS and NRM of 48% and 30%, respectively. We demonstrated that compared to a baseline model, the addition of the HCT‐CI did not improve its ability to predict OS, while substituting individual comorbidities, that is, an unweighted comorbidity score, resulted in significant improvement in model performance. The factors associated with inferior outcomes were used to develop an AYA‐specific risk score. Conclusions: The comorbidities included in the HCT‐CI as well as additional risk factors seen in younger populations need to be studied in prospective studies with the goal of validating and refining a risk score specific to AYA patients undergoing allogeneic HSCT.